The innovative team : unleashing creative potential for breakthrough results - Grivas, Chris, 1965-; Puccio, Gerard J. (San Francisco, CA : Jossey-Bass, 2012)
'Supposedly, our high level of cognition (and strategically placed thumbs) is what set us apart from much of the natural world. But it turns out that while we all think, we do not all think the same way. We all naturally use the universal creative process, for instance, but our preferences within that process make all the difference in forging a workable solution. These preferences have an enormous impact on the ways we go about solving problems and how we work together. This book introduces a uniquely effective set of tools called FourSight, field-tested by top consultants, but never before presented to a mass audience, that can help anyone from professionals to laymen solve problems and achieve performance breakthroughs. FourSight enables teams to understand their patterns of thinking and to then more deliberately manage themselves toward accomplishing a task. In business-fable style, the book reveals the impact that our underlying work style preferences have on our teams and their results. Part 1 travels along on a team's journey from dysfunctional to high functioning. Part 2 reveals the theory behind successful breakthrough teams with a clear introduction to the four stages of the breakthrough thinking process. These stages will help both team members and leaders understand the dynamics present within their team and provide the reader with options for how to improve performance. It will also serve as a great resource for management and leadership development professionals, team leaders, and others interested in kick-starting innovation in their workplaces and lives'--
Includes bibliographical references.
Keywords: Problem solving; Creative thinking; Creative ability in business; Teams in the workplace -- Management